2008
DOI: 10.1149/1.2885016
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Al–Mg Alloy Powders

Abstract: Aluminum–magnesium alloys can potentially be used as hydrogen storage materials. In order to enhance the kinetics of hydrogenation, it is desirable to have agglomerates of fine powders with very small grain size. Electrodeposition is a viable method to produce pure powders with an ultrafine structure. In this paper we report the effect of magnesium content, electrolyte temperature, and current density on the characteristics of Al–Mg deposits produced galvanostatically using an organometallic-based electrolyte.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 24 publications
3
36
0
Order By: Relevance
“…At higher compositions two intermetallics namely Al 3 Mg 2 and Al 12 Mg 17 are found in Al-Mg system. The absence of any intermetallics in the present deposits at such high composition values suggests that the deposition rates are so high that the deposition took place in non-equilibrium manner resulting in supersaturated and metastable phases [13].…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…At higher compositions two intermetallics namely Al 3 Mg 2 and Al 12 Mg 17 are found in Al-Mg system. The absence of any intermetallics in the present deposits at such high composition values suggests that the deposition rates are so high that the deposition took place in non-equilibrium manner resulting in supersaturated and metastable phases [13].…”
Section: Discussionmentioning
confidence: 78%
“…This shows that an inverse relationship exists between current density and grain size of the depositing morphologies. Our earlier results suggested that the Mg in the electrolyte [15] and thus in the deposits [13] increases with both current density and deposition time. Consistently, the smooth globules possessed higher amount of Mg (~20 at.% Mg) than feather-like morphology (Figure 2(a)).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…For this reason, electro-deposition has been studied as an alternative method to form Al alloy successfully. [11][12][13] Although it is well known that Al could be formed in Zebra battery cells, there is no reports treating Al deposition in the cathode current collectors of Zebra battery even without cell failure. Interestingly, Al-Ni alloy codeposition was reported to occur in the NiCl 2 / AlCl 3 /EMImBr (0.03/2/1) solution at 0.3 V higher voltage 14) than that of pure Al deposition.…”
Section: Introductionmentioning
confidence: 99%